UPAYA MENINGKATKAN HASIL BELAJAR SISWA KELAS V PADAMATA PELAJARAN ILMU PENGETAHUAN ALAM MELALUICOOPERATIVE LEARNING TEKNIK JIGSAWDI SD 1 PANJANGREJO - Maryati, Tri Kurniyati, Anggar Budi A. (Pelita - Jurnal Penelitian Mahasiswa UNY, 2008)
The school-based curriculum (KTSP) enables the schools to developthe available resource based on the school condition. As a result, the schoolsare provided authority in deciding the minimum mastery criteria. Theminimum mastery criteria applied in SD I Panjangrejo to science subject is65. In fact, the learning output for students Grade V is below this criteria.One of the reasons is that the teachers often use lecturing method. Thismakes the students passive and tend to keep silent. To overcome thisproblem, the reseacher applied Cooperative Learning by using Jigsaw.The aim of this research is to improve the learning output andstudents’ participation in the teaching and learning process in the class. Thisaction research used Kemmis and Mc. Taggart model. The subject of theresearch was students of SD I Panjangrejo Grade V. The change andimprovement of the treatment were monitored by using test and observation.This research employed descriptive-qualitative method.The result of the research shows the improvement of learning output,that is 63.6 before the treatment and 76.2 after getting the treatment in thefirst cycle and 81.2 in the second cycle. It means that the students havereached the minimum mastery criteria. In addition, the students’sparticipation increases from the highest criteria, 69% in the first cyclebecomes 91% in the second cycle. The medium criteria, 25% in the first cyclebecomes 9% in the second cycle, and the lowest criteria, 6%, in the first cyclebecomes 0% in the second cycle.Key word: Cooperative Learning, action research, Jigsaw technique,minimum mastery criteria